Novel mechanisms of microbial crosstalk with skin innate immunity. Issue 10 (21st July 2021) - Chinnappan, Mahendran; Harris‐Tryon, Tamia A.
Abstract: Skin is an organ with a dynamic ecosystem that harbours pathogenic and commensal microbes, which constantly communicate amongst each other and with the host immune system. Evolutionarily, skin and its microbiota have evolved to remain in homeostasis. However, frequently this homeostatic relationship is disturbed by a variety of factors such as environmental stress, diet, genetic mutations, and the microbiome itself. Commensal microbes also play a major role in the maintenance of microbial homeostasis. In addition to their ability to limit pathogens, many skin commensals such as Staphylococcus epidermidis and Cutibacterium acnes have recently been implicated in disease pathogenesis either by directly modulating the host immune components or by supporting the expansion of other pathogenic microbes. Likewise, opportunistic skin pathogens such as Staphylococcus aureus and Staphylococcus lugdunensis are able to breach the skin and cause disease. Though much has been established about the microbiota's function in skin immunity, we are in a time where newer mechanistic insights rapidly redefine our understanding of the host/microbial interface in the skin. In this review, we provide a concise summary of recent advances in our understanding of the interplay between host defense strategies and the skin microbiota.